A Systems Thinking Approach: Barriers to Implementation of an HIV-to-HIV positive transplant program in the State Sector of South Africa. (July 2018) - Kumar, Komal; Reyneke, Maryn; Du Toit, Tinus; Thompson, Dave; Barday, Zunaid; Manning, Kathryn; Okpechi, Ike; Wearne, Nicola; Muller, Elmi
Abstract : Background: Since 2008 HIV-to-HIV deceased donor kidney transplants (DDKT) have been offered in South Africa. They have proven to be a successful treatment option for patients living with both HIV and ESRD. Methods: Using systems thinking approach and a socio-ecological model framework we identified barriers for patients with (WH) and without HIV (WOH) throughout the state sector DDKT pathway in order to increase the full potential of HIV-to-HIV transplantation in South Africa. Results: Barriers identified in the DDKT pathway are limiting patients WH and WOH from achieving transplantation. Common barriers identified that affect both patients WH and WHO include: limited access to dialysis and low donation consent rates. In order to target these barriers, a socio-ecological model framework was constructed to identify key stakeholders at various levels (individual, interpersonal, organizational, community, public policy) that can impact the current system. Conclusions: Multilevel and systemic interventions will be necessary to realize the full potential of a HIV-to-HIV deceased donor kidney transplant program in South Africa. Figure. No caption available. Figure. No caption available.